ASOSIASI EBONI (Diospyros celebica Bakh.) DENGAN JENIS POHON LAIN PADA SEBARAN ALAMNYA DI SULAWESI TENGAH - Wulandari, Retno; Kustiawan, Wawan; Sukartiningsih, Sukartiningsih; Simarangkair, B.D.A.S. (Universitas Tadulako, 2016)
The obyectives of this research were to investigate the species of trees growing well along with Ebony and their level of association in the nature habitat of Ebony in Donggala, Parigi Moutong and Poso, Central Sulawesi. The research was conducted during April to Juni 2015 at Desa Siweli, Donggala; the Nature Reserve Pangi Binangga, Parigi Moutong and Tambaro Forest Coservation, Poso. The research was 30 plot in each location. There are 22 species of found growing well along with the Ebony in Donggala, 19 species of trees in Parigi Moutong and 7 species of trees in Poso. The species was found inthe 3 locations is Durio zibethinus Merr. renga pinnata (Wurmb.) and Cananga odorata H.f. & T. Were found in bouth Donggala and Parigi Moutong but not found in Poso. The species of trees were found, positively associated with Ebony. In the 3 locations, the indeks of association (Oi) is about low to very low level of association (0,13 – 0,46), so that its not indicated the presence of Ebony with those trees.Keywords: Association, Ebony, Diospyros celebica Bakh, Central Sulawesi